Persepsi Mahasiswa Pendidikan Matematika terhadap Pelaksanaan Perkuliahan Online di Masa Pandemi Covid-19 - Hesty Marwani Siregar; Syarifah Nur Siregar; Titi Solfitri (SAP (Susunan Artikel Pendidikan), 2021)
The spread of the Coronavirus has resulted in lecture activities that are usually carried out face-to-face to be carried out online. Therefore, students' perceptions of online lectures need to be known. The purpose of this study is to explain the perceptions of Mathematics Education student of Universitas Riau towards the implementation of online lectures during the Covid-19 pandemic. This study uses a descriptive quantitative approach. The data obtained from students was the perception score of students. The results obtained indicated that the implementation of online lectures had received a positive response, which was in the medium, high, and very high category. Judging from the indicators used in each aspect studied, then: 1) in the aspect of students' perceptions of themselves during online lectures, 3 indicators were in the sufficient category and 1 indicator was in the less indicator; 2) on the aspect of perception regarding the ideal online learning process, 1 indicator was in the very good category, 1 indicator was in a good category, and 2 indicators were in the sufficient category; 3) on the aspect of perception related to online learning that occurs, 2 indicators were in the sufficient category and 2 indicators were in the very poor category.